"Cold caramelization" of glucosamine under UV-C radiation. (October 2022) - Zou, Fuyao; Hrynets, Yuliya; Roopesh, M.S.; Betti, Mirko
Highlights: Glucosamine non-enzymatic browning under UV-C radiation at 25°C was studied. No neo-formed contaminants were detected in caramels within 120 min of exposure. No short-chain alpha-dicarbonyls were detected in UV-C exposed GlcN caramels. Abstract: The non-enzymatic browning of glucosamine (GlcN) under UV-C radiation at 25°C, referred to as "cold caramelization", was examined. Several UV-C exposure times of 0, 20, 60, 120 min at two GlcN concentrations of 15% and 30% were chosen. The physicochemical properties, quantitation of α-dicarbonyl compounds and polyhydroxyalkyl pyrazines, alkylimidazoles and 5-hydroxymethylfurfural were determined in UV-C exposed GlcN caramels. The results revealed the possibility of generating GlcN caramel containing desirable compounds by applying UV-C. Longer UV-C exposure time produced caramel with higher content of glucosone and 3-deoxyglucosone, as well as the GlcN self-condensation products, fructosazine and deoxyfructosazine. Importantly, none of the tested neo-formed contaminants were detected in resulted caramels. Thus, UV-C treatment may be a newly advantageous method for producing GlcN caramel. Graphical abstract: Image, graphical abstract